INDUKSI TANAMAN POLIPLOID TALAS (COLOCASIA ESCULENTA L.) DENGAN PERLAKUAN ORIZALIN SECARA IN VITRO - Wulansari, Aida; Martin, Andri F; Ermayanti, Tri Muji (Perhimpunan Biologi Indonesia, 2016)
ABSTRACTGenetic improvement of taro (Colocasia esculenta L.) is one of important research program to increase productivity and give better cultivation on the marginal land. Induction of polyploid plants is a method useful to increase genetic diversity. The aim of this research was to induce polyploid taro by oryzalin treatment. Polyploidy was induced from in vitro diploid taro ?bentul? using oryzalin at 7.5; 15; 30; 60 and 75 ?M soaked for 3 days. Regenerated shoots were grown on MS medium containing 2 mg/l BAP, 1 mg/l thiamine and 2 mg/l adenine. Shoot growth was recorded four weeks (subculture-0), eight weeks (subculture-1) and twelve weeks (subculture-2) after treatments. The results showed that survival rate of treated shoots was 100%. Higher oryzalin concentration reduced the proliferation of shoots, petiole length, numbers of leaves as well as the numbers of roots. Ploidy levels analysis determined by flowcytometer for 122 plantlets were investigated. The results indicated that control shoots were diploid. All treated shoots were polyploids. Oryzalin at 60 ?M gave 50% of tetraploid planlets, 30 ?M of oryzalin gave 5.71% hexaploids, 60 ?M of oryzalin gave 9.09% octaploids. All acclimatized plantlets gave 100% survival rate.Keywords : Colocasia esculenta L., taro, in vitro induced polyploidy, oryzalin